Pengaruh Jarak Tanam Dan Penggunaan Mulsa Terhadap Pertumbuhan Dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Kun Rawan Sari; Umar Battong; Abdul Rahing (EnviroScienteae, 2020)
The study was conducted in Pepara Village, Tanah Grogot District, Paser Regency. The research was conducted from October 2018 to February 2019. The purpose of this study was to determine the effect of planting distance and mulch use on the growth and yield of cayenne pepper (Capsicum frutescens L.). This research was in the form of an experiment using a Randomized Block Design arranged in factorial two factors with three replications. The first factor is the treatment of plant spacing with three levels, namely j1 = 60 x 60 cm, j2 = 60 x 70 cm, j3 = 60 x 80 cm. The second factor is the use of mulch which consists of 3 levels, namely m1 = no mulch, m2 = rice straw mulch, m3 = silver black plastic mulch.  Based on the results of the study showed the results that plant spacing had a very significant effect on the height of Chilli plants at the age of 2 MST and 4 MST, the number of productive branches, the number of fruits per crop of the second harvest sample, the weight of the fruit per crop of the second harvest sample, weight of fruit per bed and weight of fruit per hectare. The use of mulch also has a very significant effect on plant height at ages 2 MST, 4 MST, number of productive branches, the weight of fruit per crop of the second harvest sample, weight of fruit per bed and weight of fruit per hectare. While the interaction between the two plant spacing treatments with the use of mulch had no significant effect on plant height at ages 2 MST, 4 MST, 6 MST, the number of proactive branches, the number of fruit planted samples, the weight of fruit planted samples, fruit weight per bed and fruit weight per hectare.